95-95-95 HIV indicators among children younger than 15 years in South Africa: results from the 2017 national HIV prevalence, incidence, behaviour, and communication survey - Rindidzani E. Magobo; Musawenkosi Mabaso; Sean Jooste; Lesiba Molopa; Inbarani Naidoo; Leickness Simbayi; Khangelani Zuma; Nompumelelo Zungu; Olive Shisana; Sizulu Moyo (AIDS Research and Therapy)
Abstract Background Early detection and initiation of care is crucial to the survival and long-term well-being of children living with HIV (CLHIV). However, there remain challenges regarding early testing and linking of CLHIV for early treatment. This study examines the progress made towards achieving the 95-95-95 HIV indicators and associated factors among CLHIV < 15 years in South Africa. Methods The data was collected as part of the 2017 cross-sectional, multistage cluster randomized population-based household National HIV survey. Age-appropriate structured questionnaires were utilized to gather sociodemographic data, HIV-related knowledge, risk behaviours, and health-related information. Blood samples were collected to test for HIV serology, viral load suppression, and antiretroviral usage. Backward stepwise multivariable generalized linear regression models were fitted to identify factors associated with the 95-95-95 HIV indicators. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) are shown, and p < 0.05 indicates statistical significance. Results A total of 12,237 CLHIV < 15 years were included (median 8 years, interquartile range 4–11 years). HIV prevalence was 2.8% (95% CI: 2.4–3.3). Overall, 40.0% of the CLHIV were tested and knew their status (first 95%), and among these, 72.6% (95% CI: 61.7–81.3) were on antiretroviral therapy (ART) (second 95%), and 95.0% (95% CI: 88.4–97.9) of these were virally suppressed (third 95%). Among CLHIV, the odds of testing and knowing the HIV-positive status were significantly higher among children whose health was rated as fair/poor than excellent/good [AOR = 1.32 (95%CI: 1.05–1.67), p = 0.022], and were significantly lower among females than males [AOR = 0.82 (95% CI: 0.71–0.95), p = 0.009], and were significantly lower among those attending private healthcare facilities than public health facilities [AOR = 0.64 (95% CI:0.57–0.74), p < 0.001]. Among those who knew their HIV-positive status, the odds of being on ART were significantly higher among children residing in farm areas than urban areas [AOR = 1.40 (95% CI:1.05–1.86), p = 0.017], and were significantly lower among children attending private healthcare facilities [AOR = 0.44 (95% CI:0.36–0.54), p < 0.001]. Conclusions Awareness of HIV status and initiation of treatment in children was low. The findings highlight the need to improve HIV status awareness and disclosure to children. The findings underscore the need for targeted interventions and programs tailored for CLHIV in urban areas.